2009
DOI: 10.1177/0363546509341829
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral and Patellofemoral Kinematics After Reconstruction of an Isolated Posterior Cruciate Ligament Injury

Abstract: Background The actual in vivo tibiofemoral and patellofemoral kinematics of the posterior cruciate ligament (PCL)-reconstructed knee joint are unknown. Hypothesis Current single-bundle PCL reconstruction is unable to correct the abnormal tibiofemoral and patellofemoral kinematics caused by rupture of the ligament. Study Design Controlled laboratory study/case series; Level of evidence, 4. Methods Seven patients with an isolated PCL injury in 1 knee and the contralateral side intact were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
4
42
0
Order By: Relevance
“…Finally, static measurement of AP translation through an arthrometer does not always correlate with AP translation measured during physiological loading of the knee [16,33]. However, the tibiofemoral kinematics of seven of the included patients have been measured as well during weightbearing knee flexion using a combined MR and dual fluoroscopic imaging technique [7]. The combined distal and proximal tibial fixation technique restored the AP tibial translation to levels similar to those of the contralateral knee, indicating the graft fixation indeed provides stable reconstruction during weightbearing flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, static measurement of AP translation through an arthrometer does not always correlate with AP translation measured during physiological loading of the knee [16,33]. However, the tibiofemoral kinematics of seven of the included patients have been measured as well during weightbearing knee flexion using a combined MR and dual fluoroscopic imaging technique [7]. The combined distal and proximal tibial fixation technique restored the AP tibial translation to levels similar to those of the contralateral knee, indicating the graft fixation indeed provides stable reconstruction during weightbearing flexion.…”
Section: Discussionmentioning
confidence: 99%
“…The mean ± SD time between injury and surgery was 3.1 ± 5.5 years (range, 1.5 months to 21 years). Seven of the 10 included patients were included in our previous study of the tibiofemoral and patellofemoral kinematics after reconstruction of an isolated PCL injury [7]. The minimum followup was 1 year (mean, 2.5 years; range, 1.0-4.8 years).…”
Section: Methodsmentioning
confidence: 99%
“…MRI has also been used to determine the patellofemoral cartilage contact (Brossmann, et al, 1993; Derasari, et al, 2010; Kujala, et al, 1989; MacIntyre, et al, 2006; Powers, et al, 1998; Sheehan, et al, 1999). Recently, dual-fluoroscopic imaging systems (DFIS) have been used to measure the patellofemoral contact kinematics as well as the cartilage contact deformation during weight-bearing knee flexion (Gill, et al, 2009; Nha, et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, recent investigations have sought to describe the effects of combined PCL/PLC injury on knee kinematics as well as the biomechanical consequences of surgical reconstruction of these structures. 2,3,9,14,15 Furthermore, investigators have also developed an interest in other factors that may influence knee stability including femoral and tibial shapes. Previous work has demonstrated that increasing tibial slope via osteotomy can result in an anterior shift of the tibia and reduce tibial sag in the PCL-deficient knee.…”
mentioning
confidence: 99%